IMPACT OF IMPROVED MULBERRY GENOTYPES ON COCOON PRODUCTION IN ACIDIC SOILS OF HILLS AND FOOT HILLS - GHOSH, M.K.; CHAKRABARTI, S.P.; NATH, SHIV; GHOSH, P.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
In order to screen /identify mulberry variety with high leaf productivity and quality suitable for cultivation in acidic soils of hill/ foot hills of West Bengal nine short listed improved genotypes and BC259 as’check were grown at two locations viz. Matigara-Siliguri (foot hills) and Kalimpong (hills) with soil pH ranging from 4.6 to 5.8 were evaluated by conducting silkworm rearing. Yield of 10,000 larvae by number and weight, single cocoon weight, shell weight and shell % were found significantly superior in Tr-23, with an yield potential of 24 and 14 mt/ha/year at Matigara and Kalimpong, repectively.